The Perspective of Singapore Analysis into The Usefulness of Information As Provided in Annual Reports - Chen, Ee Hsin (2005)
This study assesses the usefulness of both quantitative and qualitative information as provided in annual reports from the perspective of analysts based in Singapore. The Financial Accounting Standards Board statement of financial accounting concepts number one and two have been used to define the determinants of usefulness assessed by means of adequacy, relevance and reliability evaluations made by financial analysts concerning disclosure. Findings from the study suggest that the majority of respondents were happy with the information supplied in the annual report. However, the financial information contained within the annual report is just an important but somewhat limited part of a range of corporate disclosure process and analysts' earnings forecasting or investment decision making process. Evidence suggests that corporate disclosure levels in Asia are generally lower and less consistent amongst firms across different industries than that of developed economies. Furthermore, although narratives are generally used for deriving assumptions for forecasting purposes, it does not replace the use of accounting data.